An Analysis of the Implementation of Differentiated Instruction in English Teaching in Sekolah Penggerak : A Case Study at SMPN 1 Batusangkar - Hendra, Jihan Febriani; Sari, Senorica Yulia (Journal of English Language Teaching, 2025)
Differentiated instruction emerges as a solution to accommodate the diversity of students. This approach emphasizes adjusting the materials, activities, and assignments of learning to the individual characteristics of students. The purpose of this study is to analyze in depth the implementation of differentiated instruction at SMPN 1 Batusangkar. This study used a qualitative research with a case study design. Observation and interview with teacher A at SMPN 1 Batusangkar are used to collect the data. The findings showed that differentiated instruction in this school is carried out systematically and structured. First, in the aspect of understanding, teacher A has a deep and comprehensive understanding. Second, teacher A’s lesson planning is based on data from the diagnostic assessment, and managed systematically. Next, teacher A uses varied strategies, technology in delivering materials, consistent use of active and collaborative learning models. Last, in support system aspect, there are special training for the teachers, intensive assistance from supervisors and education offices, and having the Merdeka Teaching Platform.